Genetic diversity and structure of two species of Enyalius (Squamata: Leiosauridae) from neotropical biodiversity hotspots - Vargas, Sarah M.; Santos, Marcelo de Oliveira; Novelli, Iara Alves; Varela-Rios, Celso Henrique; Lima, Lúcio Moreira Campos; Lucas, Priscila da Silva; Cozendey, Pilar; Paiva, Raquel Morais; Gomides, Samuel Campos; Malaguti, Sara; Sousa, Bernadete Maria de (Phyllomedusa: Journal of Herpetology, 2015)
Genetic diversity and structure of two species of Enyalius (Squamata: Leiosauridae) from neotropical biodiversity hotspots. Enyalius, a lizard genus endemic to South America, is mostly distributed in the remains of the Atlantic Forest and in the Cerrado. The genus has been the topic of a few studies but none has quantified the genetic diversity and structure within and among populations of Enyalius. The genetic diversity and structure of populations of E. bilineatus (N = 20) and E. perditus (N = 28) are examined using a 234-bp fragment of the cytochrome b gene and compared with the sequences reported in other published data. Nineteen distinct haplotypes (eleven for E. perditus and eight for E. bilineatus) were found, eight of which were recorded for the first time. The haplotype diversities are highly similar for both species (0.684 for E. perditus and 0.647 for E. bilineatus). The genetic distance between the two species is 20.3% and the distance within species is 2.0% and 5.6% for E. perditus and E. bilineatus, respectively. Our data suggest that populations of E. bilineatus are genetically divergent and may reveal cryptic diversity. This is the first study to quantify the genetic diversity of species of Enyalius from Neotropical biodiversity hotspots. These data facilitate a better understanding of both within and among population variation, and highlight the distribution of genetic lineages of an endemic and poorly studied genus.